1980
DOI: 10.1073/pnas.77.2.725
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of the major lens membrane protein.

Abstract: The biosynthetic activity of a polyribosomal fraction isolated from the lens fiber plasma membrane-cytoskeleton complex by DNase I treatment has been assayed. After translation of these pol ribosomes in a reticulocyte cellfree system and analysis of the products by electrophoresis in sodium dodecyl sulfate gels, tfe preferential synthesis of a protein with an apparent molecular weight of 26,000 was observed. By means of immunochemical characterization we showed that this protein, which seems not to be synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…In lens fiber cells, actin filaments have been shown by a number of criteria to be closely associated with the plasma membrane (1,33,35,36). The disruption of the actin filament system inhibits lens differentiation in vitro as shown by the cessation of cellular elongation (28).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In lens fiber cells, actin filaments have been shown by a number of criteria to be closely associated with the plasma membrane (1,33,35,36). The disruption of the actin filament system inhibits lens differentiation in vitro as shown by the cessation of cellular elongation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional peptide mapping reveals that whereas a-spectrins from chicken erythrocytes, brain, and lens are highly homologous, the 3"-spectrins, although related, have some cell-type-specific peptides and are substantially different from erythrocyte 1% spectrin. Thus, the expression of cell-type-specific 3'-and /3-spectrins may be the basis for the assembly of a spectrin-plasma membrane complex whose molecular composition is tailored to the functional requirements of the particular cell-type.The cytoskeleton of vertebrate lens cells is composed of microtubules, actin filaments, and vimentin-type intermediate filaments (5,20, 21,33,34,36). Recent studies have indicated that the lens cytoskeleton may play an important role in lens differentiation.…”
mentioning
confidence: 99%
See 3 more Smart Citations